The Marketing Strategy and Florist Business Development at Little Puff Florist - Endah Cahyaning Astuti; Ma’mun Sarma; Joko Purwono (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
The florist industry has experienced significant growth in recent years, particularly due to increased consumer interest in flowers as part of home decor, gifts, and special events. However, the competitive market and changing consumer preferences demand that florists adopt effective marketing strategies and understand the internal and external factors that can impact their business. By leveraging internal strengths and external opportunities, while addressing weaknesses and threats, florists can design effective strategies for business development. The methods used in this study are qualitative with a case on Little Puff Florist. SWOT analysis (Strengths, Weaknesses, Opportunities, Threats) is utilized to identify internal and external factors, and QSPM (Quantitative Strategic Planning Matrix) decision stage to evaluate alternative strategies based on internal and external success factors. The alternative strategies for Little Puff include improving customer service, enhancing marketing through digital technology, and developing products with new innovations. The marketing and development strategies employed by Little Puff are market penetration and product development. The SWOT analysis indicates maintaining product quality, improving service, enhancing product development, and maintaining customer trust.